Analysis of skull morphometric characters in diurnal raptors (Accipitriformes and Falconiformes) - Pecsics Tibor (Ornis Hungarica, 2019)
Diurnal birds of prey (Accipitriformes and Falconiformes) has traditionally been known as comprising a single order. Recently, this classification has been used in the non-taxonomic sense as referring to a convergent group of birds that are largely classified as predatory birds. Although these birds are similar in their morphology, the species differ in their foraging methods and prey preference. The cranial shape and the physical attributes determine the efficiency of the resource use. The aim of this study is to increase our knowledge of the relationship between skull shape, prey preference, and foraging habits. A geometric morphometric approach was used to analyse two-dimensional cranial landmarks. We used principal component (PC) analyses on measurements that may be related to prey preference and foraging habits. The PCs are resulted described the relative height of the skull and beak, the variation in the relative size, the orientation and robustness of the lacrimal bone, the variation in the relative size of the neurocranium compared to the viscerocranium, and the orientation of the palatine bone. The dietary categories significantly overlap. The skull morphology reflects more on foraging habits than diet or prey preference.